2018
DOI: 10.1016/j.cep.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal gas-phase pulsed corona discharge for lignin modification

Abstract: Lignin has the potential to become a significant resource of renewable aromatics for the chemical industry. The current work studies pulsed corona discharge (PCD) as an alternative method for lignin modification. The effect of initial lignin concentration and gas phase composition on aldehydes formation was studied experimentally. Kraft lignin was used as a test compound. It was concluded in the work, that treatment in low oxygen content atmosphere and high initial lignin concentration leads to higher lignin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recent work showed that higher lignin content and lower % O 2 lead to less harsh conditions favoring the aldehyde formation over the ring cleavage and lignin degradation. 154 A high degree of lignin oxidation, inferred by the concentration of carbonyl and carboxyl groups, was also observed. Clearly, understanding plasma-lignin interactions as a function of plasma processing conditions can lead to more controlled product distribution.…”
Section: Plasma-cellulose Interactionsmentioning
confidence: 88%
“…Recent work showed that higher lignin content and lower % O 2 lead to less harsh conditions favoring the aldehyde formation over the ring cleavage and lignin degradation. 154 A high degree of lignin oxidation, inferred by the concentration of carbonyl and carboxyl groups, was also observed. Clearly, understanding plasma-lignin interactions as a function of plasma processing conditions can lead to more controlled product distribution.…”
Section: Plasma-cellulose Interactionsmentioning
confidence: 88%
“…They found that the surface of lignin oxidized in oxygen plasma atmosphere creating hydroxyl, carbonyl, and carboxyl groups while in an Ar-plasma the reduction of the surface was observed. Sokolov [127] used pulsed corona discharge (PCD) for the modification of lignin and showed that during treatment, lignin oxidized to aldehydes, and oxidative cleavage of aromatic rings occurred. However, the precise nature of the changes in the structure remained unclear.…”
Section: • Ligninmentioning
confidence: 99%